REPRESENTASI KEKERASAN DALAM FILM DOKUMENTER THE ACT OF KILLING - Lumbangaol, Rona Yuni Cipaini; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2021)
The documentary film The Act Of Killing "Jagal" requires the meaning of the sadism of the massacre and its implicit and explicit messages, whether seen from the dramatic literary, language and artistic aspects. This documentary film was released in 2012 which tells of the sadism of the massacre carried out by Anwar Congo and his friends as anti-PKI people against people accused of being communists, Chinese ethnicity, and intellectuals in less than one year, after the PKI was accused by the TNI as perpetrators of GS30 in 1965 in Indonesia, right in the area of Deli Serdang Medan. This study aims to determine and describe the representation of the sadism of the massacres in each scene of the massacre in the documentary film The Act Of Killing "Jagal" which is reviewed by the semiotic triangle meaning theory of Charles Sander Peirce. This research was conducted using a qualitative approach, to answer this research. , the author uses a qualitative method with Peirce's semiotic approach. The object of research is the video recording of the documentary film the acr of killing "Jagal" and the unit of analysis is the pieces of the image in the film which are believed to represent the sadism of the massacre. Based on the interpretation results using Peirce's semotic approach. The icons, indexes and symbols in the film the act of killing “Jagal” tell about how the violence perpetrated by the perpetrators of the anti-murder of PKI members and the heroic attitude of the perpetrators towards the killings that were committed.